The Hierarchy of Needs of Miyamoto Musashi in Eiji Yoshikawa's Novel - Rahman, Aulia; Devi, Rima; Rahayu, Rachmidian; Nesa, Fakhria (Universitas Airlangga, 2025)
This study aims to reveal the psychological aspects of the main character in Eiji Yoshikawa’s novel Musashi, using Abraham Maslow’s Hierarchy of Needs theory. Using qualitative descriptive methods and a literary psychology approach, this study analyses how Musashi’s life struggles illustrate his efforts to fulfil the five levels of human needs, namely physiological needs, safety, love and belonging, self-esteem, and self-actualization. The results show that Musashi’s character development is a complex and gradual process, beginning with his efforts to survive physically after the war, his search for moral purpose through the guidance of Takuan Soho, his inner conflict regarding his relationship with Otsu, and concluding with his search for recognition through the battles he fought. The culmination of this achievement is when Musashi realizes that the true victory is not defeating opponents but controlling oneself. This understanding underwent a comprehensive psychological change in line with the fulfilment of needs at each level of Maslow’s hierarchy. With a literary psychology approach, Musashi is not only understood as a story revolving around battle and honour, but also as an existential narrative about a person struggling to achieve self-recognition. This research offers a deeper insight into the relationship between psychology and literature, demonstrating that fictional characters created by authors can illustrate the dynamics of personality that humans also experience in general.